Determinação molecular de resistência genotípica primária do Helicobacter pylori à claritromicina e fluoroquinolonas em amostras gástricas obtidas por endoscopia digestiva alta no Brasil - Bruno Squarcio Fernandes Sanches (2016)
INTRODUCTION: In addition to the incomplete adherence to treatment, the main factor associated with therapeutic failure in the treatment of Helicobacter pylori (HP) is bacterial resistance to antimicrobials, mainly acquired by genetic mutations. The detection of the prevalence of these mutations is critical to the understanding of bacterial resistance rates and adequacy of treatment regimens. OBJECTIVE: To estimate the prevalence of HP's primary resistance to clarithromycin andfluoroquinolones through a molecular test on convenience samples collected in five regions of Brazil. METHODS: We selected six endoscopy centers in the country, 519 patients with positive rapid serologic test for HP (65.7% women, mean age 43 [range 19-79] years), not previously treated for this infection. All patients underwent endoscopy with biopsies of antrum and body and realization of molecular test GenoType HelicoDR (Hain Life Science, Germany) for the detection of HP and pointmutations of the genes responsible for resistance to clarithromycin andfluoroquinolones. The molecular procedure constituted of three steps: DNA extraction from endoscopic samples, multiplex amplification and reverse hybridization. Mutations more often associated with resistance to both antibiotics were evaluated. RESULTS: Twenty-nine patients were excluded for lack of infection by HP to molecular testing (21 cases) and no gyrA band (08 cases). In total, the resistance to clarithromycin was detected in 83 samples (16.9%) and fluoroquinolones in 66 samples (13.4%). In the regions studied, resistance to clarithromycin andfluoroquinolones was respectively 16.6% and 2.7% in the North (Manaus), 14.5% and 13.7% in the Northeast (Salvador and Maceio) 19.2% and 15.4% in the Midwest region (Goiania), 17.5% and 13.8% in the Southeast (Belo Horizonte) and 19.1% and 16.4% in the South (Porto Alegre). The point mutation A2147G was the most common (90.3%) among strains resistant to clarithromycin. In resistant to fluoroquinolones group, the mutations not specified by the method were the mostcommon (37.8%), followed by the D91N mutation (34.8%). Genotypic heterogeneity was observed in 25.3% of samples. The double resistance to clarithromycin and fluoroquinolones was found in 4.3% of cases (n = 21). CONCLUSION: In Brazil, primary genotypic resistance to clarithromycin HP is situated in the borderland (15 to 20%) where clarithromycin-containing triple therapies are suggested to be empirically12 used. The primary resistance to fluoroquinolones also shows growing and worrying levels. Molecular testing is an appropriate and feasible diagnostic tool for the determination and monitoring of primary genotypic resistance of HP to antibiotics.